Psychology as a Social Science - Bissau-Diener, Robert; Diener, Ed (Open textbook library., 2015)
This textbook provides standard introduction to psychology course content with a specific emphasis on social aspects of psychology. This includes expanded content related to social cognition, aggression, attraction and similar topics. This book can be modified: feel free to add or remove modules to better suit your specific needs.Please note that the publisher requires you to login to access and download the textbooks.